"Still they remember me" - Dana, Carol A.; Lukens, Margo; Quinn, Conor M. (Native Americans of the Northeast., 2021)
"Newell Lyon learned the oral tradition from his elders in Maine's Penobscot Nation and was widely considered to be a "raconteur among the Indians." The thirteen stories in this new volume were among those that Lyon recounted to anthropologist Frank Speck, who published them in 1918 as Penobscot Transformer Tales. Transcribed into current Penobscot orthography and with a new English translation, this instructive and entertaining story cycle focuses on the childhood and coming-of-age of Gluskabe, the tribe's culture hero. Learning from his grandmother Woodchuck, Gluskabe applies lessons that help shape the Wabanaki landscape and bring into balance all the forces affecting human life. These tales offer a window into the language and culture of the Penobscot people in the early twentieth century. In "Still They Remember Me," stories are presented in the Penobscot language and English side-by-side, coupled with illustrations from members of the tribal community. For the first time, these stories are accessible to scholars and a new generation of Penobscot language learners"--